AN ANALYSIS OF EXPRESSIVE ILLOCUTIONARY ACT FOUND IN JUSTICE MOVIE - Lajar, Yakobus Adriano; Candra, Komang Dian Puspita; Pratiwi, Desak Putu Eka (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2023)
This study focused in analyzing the illocutionary act found in Justice Movie. The aims of this study are to identify types of illocutionary acts that found in Justice Movie and to analyzed contexts of situation that found in Justice Movie point to the meaning of illocutionary acts. This study employed descriptive and qualitative method. The data of this study were obtained by watching and Note-taking the utterances which contained in illocutionary acts in Justice Movie. The researcher used two theories to analyze the data in this research, the first theory is from Yule (1996) to find out the types of expressive illocutionary acts in the Justice Movie, the second is the theory that proposed by Halliday and Hassan (1989) about the context of situation. There are 13 data of expressive illocutionary act found in Justice Movie such as, complimenting (3), praising (1), sorrow (2), welcome (1), blaming (1), apologizing (2), pleasure (1), dislike (1) and thanking (2).